Data-Driven Business Model Innovation in Europe: Ethical Data Practices and Ecosystem Involvement - Heikkilä, Marikka; Heikkilä, Jukka; Ahmad, Farhan (MDPI AG, 2025)
Creating, sharing, and using data are expected to lead to the development of new innovative business models. This study investigates the interplay between business model change, ethical data practices, and participation in data ecosystems in fostering data-driven innovation. Using survey data from 1200 European companies, analyzed through partial least squares structural equation modeling (PLS-SEM), the findings reveal that while firms recognize the potential benefits of data, business model change alone is insufficient to drive innovation. Instead, active engagement in data ecosystems and adherence to ethical data practices together have a significant positive impact on data-driven innovation. This research contributes to the business model innovation literature by highlighting the role of ecosystems and ethical governance in shaping sustainable data-driven innovations. This study also provides practical insights for firms seeking to transition toward more collaborative and ethically grounded data-driven business models.